ANESTHESIOLOGY, HEMATOLOGY AND SERUM CHEMISTRY OF THE GIANT OTTER, Pteronura brasiliensis (CARNIVORA, MUSTELIDAE) - Rosas, Fernando César Weber; Neto, José Anselmo d’Affonseca; Mattos, Gália Ely de (Arquivos de Ciências Veterinárias e Zoologia da UNIPAR, 2009)
There are very few hematological values of giant otters found in the literature and despite that new anesthetic drugs became available in recent years, no information has been published regarding their use in this endangered species. Therefore, to fulfill these gaps, about 15 ml of blood were collected from the jugular or femoral veins of six captive giant otters between March-July/1995 and September-November/2004. To collect the blood, the animals were anesthetized either using 5% ketamine hydrochloride (Ketalar®-Parke- Davis) combined with xylazine (Rompun®-Bayer) in a mean dosage of 8.78 ± 0.91 mg/kg and 1.92 ± 0.15 mg/kg, respectively (n=4), or using tiletamine hydrochloride and zolazepam hydrochloride (Zoletil 50® - Virbac) in a mean dosage of 1.93 ± 0.57 mg/kg, followed by an injection of atropine sulfate 1 % (Atropina® - Farmagrícola S.A.) in a mean dosage of 0.09 ± 0.02 mg/kg (n=7). The depth and time of immobilization provided by both associations allowed the accomplishment of all the veterinary procedures with satisfactory safety. The mean rectal temperature recorded during immobilization was 39.16 ± 0.59oC (n=8). The hemoglobin and packed cell volume (PCV) mean values were 16.36 ± 2.81 g/dl and 50.66 ± 7.77 %, respectively. The WBC, lymphocytes, monocytes, and eosinophils values were similar to those reported for other otter species. Similarly, the blood chemistry values were close to those found in other mustelids. Considering that all animals used in this study were clinically healthy, the hematologic and blood chemistry values here presented provide a baseline for recognition of abnormal blood values in giant otters.